Students Abroad: Preconfederation Educational Links Between Newfoundland and the Mainland of Canada - MacLeod, Malcolm (Historical Papers / Communications historiques)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1985)
AbstractIn the decades before Confederation in 1949, one important link between the Dominion of Canada and the reluctant tenth province was the increasing reliance of New- foundland students upon Canadian institutions for advanced education and training. Five volumes of Who's Who in Newfoundland, published between 1927 and 1961, provide biographical information on 344 individuals who left the colony to pursue educational opportunities abroad. The major focus for such opportunities shifted over time from Great Britain to the mainland of Canada. Institutions in the Maritime provinces drew over half of these students, while colleges and schools in Ontario received almost one-quarter. In some instances, Newfoundlanders became an impor- tant proportion of the student body at individual colleges -for example, students from western Newfoundland at Saint Francis Xavier and students from the south coast at Mount Allison. The highest proportion was probably the 15 per cent which Newfoundlander s formed in the general student body at Nova Scotia Technical College in the several years around 1940.The establishment of Memorial University College in 1925 did two things: it made Newfoundland more self-contained in matters of higher education, and it strengthened certain patterns of international linkage, especially with Canada. Fledgling Memo- rial's major formal affiliations were with the universities of the Maritime provinces: Memorial s president joined representatives of Acadia, Dalhousie, Saint Mary's, King's, Mount Allison and Saint Francis Xavier on the unified Atlantic region govern- ing body of Nova Scotia Technical College and 55 per cent of the degrees held by Memorial's preconfederation faculty members were from Canadian institutions.This paper demonstrates how natural it was for Newfoundland to be drawn within the Canadian educational orbit in the first half of the twentieth century, while charac- teristic patterns in the links that were formed between two North American countries are illustrated.